2021
DOI: 10.1136/bmjresp-2020-000817
|View full text |Cite
|
Sign up to set email alerts
|

Specialty COPD care during COVID-19: patient and clinician perspectives on remote delivery

Abstract: IntroductionThe COVID-19 pandemic has impacted specialty chronic obstructive pulmonary disease (COPD) care. We examined the degree to which care has moved to remote approaches, eliciting clinician and patient perspectives on what is appropriate for ongoing remote delivery.MethodsUsing an online research platform, we conducted a survey and consensus-building process involving clinicians and patients with COPD.ResultsFifty-five clinicians and 19 patients responded. The majority of clinicians felt able to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 16 publications
1
44
0
Order By: Relevance
“…This suggests that irrespective of the advantages of remote care, patients rely on the personal contact with physicians at regular intervals, especially as there are differences between physicians and patients regarding the perception and evaluation of clinical state. [16] On the other hand, in our study COPD patients with high symptom burden and exacerbation risk reported to avoid contact with physicians in favour of tele-consultation. This indicate that remote care should be tailored to the specific needs of a certain group of patients.…”
Section: Discussionmentioning
confidence: 50%
“…This suggests that irrespective of the advantages of remote care, patients rely on the personal contact with physicians at regular intervals, especially as there are differences between physicians and patients regarding the perception and evaluation of clinical state. [16] On the other hand, in our study COPD patients with high symptom burden and exacerbation risk reported to avoid contact with physicians in favour of tele-consultation. This indicate that remote care should be tailored to the specific needs of a certain group of patients.…”
Section: Discussionmentioning
confidence: 50%
“…It is therefore plausible that COVID-19 restrictions could reduce the incidence of COPD exacerbations [ 9 ]. However, shielding and other restrictions can have a negative impact on patients’ physical and mental health, and limit access to health care services [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, people with severe chronic lung diseases used TH apps more often than those without chronic lung diseases (OR and 95% CI: 1.23, 1.04 to 1.45) [68]. A recent study reported that clinicians were able to evaluate symptom severity (95%), promote smoking cessation (84%) and signpost to other healthcare resources (80%) [69]. Also, patients involved in the study reported that assessment of COPD severity and starting new prescriptions were being fully addressed via TH.…”
Section: Telehealth Applicationsmentioning
confidence: 99%